AN EX POST FACTO STUDY: STUDENT™ LEARNING STYLES IN BIOLOGY EDUCATION AT UNIVERSITAS JAMBI - Mursyd, Danial; Sembiring, Dian Arisandy Eka Putra; Yusuf, Muhammad; Rangkuty, Sailana Mira (Universitas Negeri Medan, 2023)
This study used an ex-post facto research methodology with a descriptive approach to assess the learning habits of biology education students at Universitas Jambi in regards to 'Work Method' and 'Delay Avoidance'. The study demonstrated similar levels of proficiency (satisfactory), with 'Work Method' scoring a 75.00% and 'Delay Avoidance' slightly reaching a score of 75.70%. These data indicated that there is a dependable yet enhanceable basis in learning habits. The study highlights the need of employing educational practices that promote organized learning and efficient time management, with the goal of enhancing students' learning habits and academic progress.